Activation of hydrogen peroxide by the nitrate anion in micellar media. Issue 5 (24th February 2021) - Schmidt, Fabian; Zehner, Bastian; Kaposi, Marlene; Drees, Markus; Mink, János; Korth, Wolfgang; Jess, Andreas; Cokoja, Mirza
Abstract : Surface-active imidazolium nitrates activate hydrogen peroxide, which enables the epoxidation of olefins. The micelles solubilise the substrate in the aqueous oxidant phase and allow for simple product separation and catalyst recycling. Abstract : We present the activation of hydrogen peroxide by micellar imidazolium nitrates via H-bond formation in water, as shown by vibrational spectroscopy and supported by DFT calculations. Mechanistic insight into the interactions of the surfactant cation, the nitrate anion and H2 O2 is given. The micelles solubilise and epoxidise cyclooctene in the aqueous phase.